2023
DOI: 10.1002/ceat.202200502
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Hydrate Formation Kinetics in the Presence of a Layered Double Hydroxide Nanofluid

Abstract: The effects of a hybrid nanofluid (Cu-Al layered double hydroxide (LDH)) on the CO 2 hydrate formation kinetics was investigated at three different nanofluid concentrations (0.25-1.0 wt %). The Cu-Al LDH nanofluid was prepared using a one-step co-precipitation technique. The addition of the LDH nanofluid reduces the induction time and enhances the hydrate formation kinetics. The maximum reduction in the induction time (by 91.08 %) was observed at the optimal nanofluid concentration of 0.5 wt %, compared to wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…The close-to-neutral pH (5 < pH < 8) can lead to the formation of aluminum hydroxide, which may exist as a suspension of nanoparticles . The formation of nanoparticles might reduce induction time by creating more nucleation sites . Sun et al reported that nonanoic acid with THF + water emulsion formed small crystal particles, eventually decreasing the induction time.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The close-to-neutral pH (5 < pH < 8) can lead to the formation of aluminum hydroxide, which may exist as a suspension of nanoparticles . The formation of nanoparticles might reduce induction time by creating more nucleation sites . Sun et al reported that nonanoic acid with THF + water emulsion formed small crystal particles, eventually decreasing the induction time.…”
Section: Resultsmentioning
confidence: 99%
“…Clathrate hydrates (hereafter hydrates) are a specific category of clathrates, where hosts are hydrogen-bonded with water molecules. 1 The hydrate studies are essential for several technological applications such as gas storage and transportation, 2 water desalination, 3 CO 2 sequestration, 4 and prevention of pipeline plugging. 5−7 Understanding hydrate formation thermodynamics and kinetics is key to the development of hydrate-based technologies.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations